The systematic position of some ethiopian nippostrongylinae (nematoda, trichostrongylina, heligmosomoidea) from the National Collection of Animal Helminths, Onderstepoort, South Africa - Durette Dusset, M. C. (2005)
The taxonomic status of some nippostrongyline nematodes deposited in the National Collection of Animal Helminths, Onderstepoort, is revised. Heligmonina boomkeri n. sp. is described from Aethomys chrysophilus from South Africa. The most closely related species by the body measurements and the pattern of the caudal bursa is Heligmonina bignonensis Diouf, Bâ & Durette-Desset, 1997, a parasite of Mastomys erythroleucus from Senegal. It differs from the new species mainly in the number of ventral cuticular ridges at mid-body (four versus five) and the left ala in the male is shorter than the body diameter. The systematic position of Heligmonina spira (Ortlepp, 1939) and Neoheligmonella capensis (Ortlepp, 1939) is confirmed here through their synlophe, which was not previously studied.